Pengaruh Literasi Keuangan Terhadap Investasi Saham - Listiawati, Elsa Laila; Rahayu, Iis; Marsela, Viona; Yuniar, Inna Pujiana; Suherman, Ujang (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Financial literacy includes the ability to look at financial alternatives, discuss money and financial matters, and plan for the future. Anyone can experience the long-term benefits of financial literacy if they have good financial literacy. In addition, people can make investment or savings decisions by understanding financial literacy. This study conducted a literature survey or literature review by collecting information using the Systematic Literature Review (SLR) method. Further discussion can focus on effective financial literacy strategies in improving investors' understanding of stock market dynamics. From this, it can be concluded that financial literacy has a crucial role in shaping wise investment decisions, and research in this regard can be expanded to explore more aspects that can improve the understanding and application of financial literacy in various economic and investment contexts.